O impacto da realização da Copa das Confederações da FIFA de 2013 e da Copa do Mundo da FIFA de 2014 na criminalidade em Belo Horizonte - Alexandre Magno Alves Diniz; Ludmila Lopes Ribeiro; Ricardo Henrique Palhares (Confins)
Much has been said about the impact of the so-called "mega-events" on their host cities. However, the literature tends to emphasize the impact of these events on the economy, infrastructure and transport network to the detriment of their social implications, especially those related to crime. Belo Horizonte, one of Brazil's main urban centers, experienced great social unrest during the FIFA Confederations Cup 2013 and the FIFA World Cup 2014, which raised concerns about the criminal incidence. This article examines, from a comparative basis the geographical incidence of robberies, thefts and damage to public and private property in Belo Horizonte, taking into account the recent historical evolution of crimes that occur during major events. Criminal data furnished by the Military Police of Minas Gerais are employed in the production of isoplethic maps and temporal graphs. The results show that, in general, the incidence of such crimes during the major events in Belo Horizonte underwent substantive changes in both temporal and spatial terms, showing high correlation with football matches.